From Learning to Decision-Making: A Cross-Sectional Survey of a Clinical Pharmacist-Steered Journal Club - Sherine Ismail; Sara Al Khansa; Mohammed Aseeri; Hani Alhamdan; K. H. Mujtaba Quadri (MDPI AG, 2017)
Journal clubs have been traditionally incorporated into academic training programs to enhance competency in the interpretation of literature. We designed a structured journal club (JC) to improve skills in the interpretation of literature; however, we were not aware of how learners (interns, residents, clinical pharmacists, etc.) would perceive it. We aimed to assess the perception of learners at different levels of pharmacy training. A cross-sectional design was used. A self-administered online survey was emailed to JC attendees from 2010-2014 at King Abdulaziz Medical City, Jeddah, Saudi Arabia. The survey questions included: introduction sessions, topic selection, JC layout, interaction with the moderator, and decision-making skills by clinical pharmacists. The response rate was 58/89 (65%); 52/54 (96%) respondents believed that JC adds to their knowledge in interpreting literature. Topic selection met the core curriculum requirements for credentials exams for 16/36 (44.4%), while 16/22 (73%) presenters had good to excellent interaction with the moderator. JC facilitated decision-making for 10/12 (83%) of clinical pharmacists. The results suggest that clinical pharmacist-steered JC may serve as an effective tool to empower learners at different levels of pharmacy practice, with evidence-based principles for interpretation of literature and guide informed decision-making.